Short Communication: Aphrodisiac plants used by Dayak Ethnic in Central Kalimantan Province, Indonesia - FAUZI FAUZI; HARTO WIDODO (Society for Indonesian Biodiversity, 2019)
Abstract. Fauzi, Widodo H. 2019. Short Communication: Aphrodisiac plants used by Dayak Ethnic in Central Kalimantan Province, Indonesia. Biodiversitas 20: 1859-1865. Sexual dysfunction in men might render psychological disorders and household harmony. The prevalence increases with age and other risk factors such as systemic diseases and psychological factors. A community with no exception certain ethnic groups uses plants to fulfill various needs, including to treat sexual disorders in men. This paper aims to explore medicinal plants that are often used for aphrodisiacs by Dayak ethnic in Central Kalimantan Province, Indonesia. The method was carried out through reviewing literature, searching for various references and analyzing data of the exploration of ethnomedicine and community-based medicinal plants in Indonesia held in 2012 and 2015. Of the 9 Dayak ethnic groups surveyed, only four ethnic groups (Bawo, Taboyan, Tomum and Siang) posses an aphrodisiac formula. The plants used by ethnic Dayaks for aphrodisiacs are Eurycoma longifolia Jack., Luvunga sarmentosa (Bl.) Kurz., Rennellia elliptica Korth., Mimosa pudica L., Lepisanthes amoena (Hassk) Leenh., Fordia splendidissima (Miq.) Buijsen., Imperata cylindrica (L.) Raeusch., Ficus deltoidea Jack., Koilodepas bantamense Hassk., Eusideroxylon zwageri Teijsm. & Binn., Gnetum sp., Caryota sp. and Calamus sp.